Composite Indicators for the Family Change: ‘Familism' vs ‘Individualism' in the International Context - Ayuso-Sánchez, Luis Manuel; De-Miguel-Luken, Verónica (My University, 2016)
The aim of this paper is to propose a composite indicator to measure ‘familism’, conformed by two main dimensions: values on one hand (duty to take care of the family, importance of the family, sacrifices for the family...) and behaviours, on the other (predominance of married couples instead of cohabitant couples, high frequency of contact among members, family support…). In contrast to this idea of ‘familism’ we find that of individualism, that defends the independence of family members, tolerance to new family models, cohabitation instead of marriage,… , that implies less frequency of interaction among relatives and more governmental intervention towards children and elderly care. We observe that a higher degree of ‘familism’ does not always match with a lower degree of individualism when both dimensions, attitudes and behaviours, are considered. For instance, we find countries which are individualist in values but not in behaviours (such as Spain), whilst others, such as Japan, are ‘familist’ both in values and behaviours and finally, others, such as Sweden, are individualist with regards to both perspectives. We propose two different methodological approaches to the question. First, we use microdata from the Family, Work and Gender Roles module of the International Social Survey Programme-ISSP (years 1994, 2002 and 2012), in which 45 countries have participated. Information for the three rounds is collected for 17 countries with very different family values and welfare systems (for instance, Sweden, Japan, Russia, Spain, United Kingdom or the United States). From this data source, we create a first index on familism that can be related to individual sociodemographic characteristics. Second, we complete it through the inclusion of macro data (such as the divorce rate per country), in order to refine comparison at a country level by adding new variables to the previous index.
Keywords: Familia; Family; Social indicators; Sociology